Comparison of incidence of anaphylaxis between sugammadex and neostigmine: a retrospective multicentre observational study. (February 2020) - Orihara, Masaki; Takazawa, Tomonori; Horiuchi, Tatsuo; Sakamoto, Shinya; Nagumo, Kazuhiro; Tomita, Yukinari; Tomioka, Akihiro; Yoshida, Nagahide; Yokohama, Akihiko; Saito, Shigeru
Abstract: Background: Although cases of anaphylaxis caused by sugammadex have been reported, its incidence remains uncertain. Conversely, no studies have evaluated the incidence of anaphylaxis to neostigmine. Methods: This was a retrospective multicentre observational study of patients who underwent surgery under general anaesthesia between 2012 and 2016 to compare the incidence of anaphylaxis with sugammadex with that of neostigmine at four tertiary hospitals in Japan. To ensure the quality of diagnosis, only cases with a clinical history suggestive of anaphylaxis, along with positive results from in vitro or in vivo testing, were assessed. Results: From a total of 49 532 patients who received general anaesthesia included in this study, 18 cases of anaphylaxis were reported, of which six were attributable to sugammadex and none to neostigmine. There were no fatalities attributable to anaphylaxis. The incidence of anaphylaxis caused by all drugs or by sugammadex was calculated as 0.036% (95% confidence interval [CI]: 0.022–0.057%) and 0.02% (of the number of sugammadex cases) (95% CI: 0.007–0.044%), respectively. Conclusions: The results suggest that neostigmine might be safer than sugammadex when assessing only the incidence of anaphylaxis. We believe that there is room for reconsideration of the choice of reversal agent for neuromuscular blocking agents by all anaesthetists. Clinical trial registration: UMIN000022365; UMIN000033561.